(untitled) (Mongolian Journal of Agricultural Sciences, 2019)
In this research work, we evaluated the level of the sustainable agricultural development of Mongolia by a criteria consisting of 3 sub-systems and 14 indicators with a multi-index comprehensive evaluation method by using the data of 2005-2017. According to the research, the sustainable agricultural development level has reached 55.53%, where the economic sub-system has the highest impact and the social sub-system has the lowest impact but the development tendency of the environmental sub-system is at the same level as the general level and the level of sustainable agricultural development strongly depends on the environmental and climatic conditions.